Neurogenic Stunned Myocardium Progressing to Takotsubo Cardiomyopathy with Milrinone - Srinivasan, Siddharth; Balakrishnan, Arjun; Nair, Rajesh P.; Menon, Girish (Journal of Neuroanaesthesiology and Critical Care, 2025)
A 67-year-old female came with acute-onset headache and altered sensorium secondary to a ruptured right giant supraclinoid internal carotid artery aneurysm. Echocardiography revealed global wall motion abnormalities. She underwent aneurysm clipping on day 4 following ictus and her postoperative Glasgow Coma Scale (GCS) score was E2VTM5. She developed an infarct in the caudate nucleus for which milrinone infusion was started. Following milrinone infusion her blood pressure dropped significantly. Despite stopping milrinone, it did not respond to noradrenaline or dopamine. Investigations revealed a troponin of 0.6 ng/mL, and electrocardiogram showed new ST-T changes in leads V3-V6. Echocardiography showed paradoxical apical excursion, suggestive of Takotsubo cardiomyopathy. She was started on vasopressin, her blood pressure stabilized, and noradrenaline was gradually tapered. Due to prolonged hypoperfusion, however, GCS dropped to E2VTM3. Eventually, inotropes were stopped, and cardiac contractility recovered. The patient had a sudden drop in GCS on postoperative day 25 and died.
Keywords: neurogenic stunned myocardium; Takotsubo cardiomyopathy; milrinone